Senior High School Second-Grade Language Students’ Perceptions on the Use of YouTube Videos - Vania Marella Sugiarto; Listyani Listyani; Ardiyarso Kurniawan (Universitas Dian Nuswantoro, 2021)
Abstract. YouTube is a website that provides a lot of videos from all over the world. Then, YouTube also offers many benefits for the educational area, such as for learning a language. This study aimed to discover a private Senior High School second-grade students’ perceptions of using YouTube videos in language learning. The participants of this study consisted of ten second graders of language programs in that Senior High School. The data in this study were gathered by distributing open-ended questionnaires and doing some semi-structured interviews. This study found that YouTube has been very familiar to the students because most students watched YouTube every day for almost five hours. However, students faced some challenges and difficulties while learning the language through YouTube videos. Hopefully, this study can be useful for teachers and students to use YouTube effectively to learn languages.Keywords: YouTube; perceptions; language-program students; language learning.Abstrak. YouTube adalah sebuah situs internet yang menyediakan banyak video dari seluruh dunia. Situs ini menawarkan banyak manfaat dalam bidang pendidikan termasuk pembelajaran bahasa. Penelitian ini bertujuan untuk mengetahui persepsi siswa kelas dua sebuah SMA swasta tentang penggunaan video dari situs YouTube dalam pembelajaran bahasa. Responden penelitian ini terdiri dari sepuluh siswa kelas 2 dari sebuah program bahasa di SMA tersebut. Data diperoleh dari kuesioner “open-ended” dan juga wawancara “semi-structured”. Dari data, ditemukan bahwa YouTube sudah sangat dikenal dikalangan siswa karena sebagian besar siswa menonton vdeo YouTube setiap hari selama hampir lima jam. Namun demikian, ada juga beberapa tantangan dan kesulitan yang di hadapi siswa saat belajar bahasa melalui situs YouTube. Penelitian ini diharapkan bisa bermanfaat bagi guru maupun siswa dalam belajar bahasa melalui YouTube sebagai sarana belajar yang efektif.Kata kunci: YouTube, persepsi, mahasiswa program bahasa, pembelajaran bahasa